Evaluasi karkas dan kualitas fisik daging babi pada tempat usaha pemotonggan ternak babi di Distrik Masni Kabupaten Manokwari - Miksen M. Sangkek; Marlyn N. Lekitoo; Hanike Monim (Cassowary, 2021)
This study aims to evaluate the carcass and examine the physical quality of pork in the local pork slaughterhouse, Masni District and the relationship between slaughter weight and carcass weight, carcass percentage, carcass length, fat, pH and cooking losses. The results showed the range of slaughtering age of local pigs from 6 - 60 months (male pigs 10-12 months old and female pigs 18-20 months old). The average sliced ​​weight had a very significant effect (P <0.01) on carcass weight, while the carcass percentage had no significant effect based on the regression analysis between cut weight and carcass percentage was Y = 63.85 + 0.1463, with a coefficient of determination (R2) of 9.43%. Cut weight had a very significant effect (P <0.01) on carcass length in regression analysis Y = 37.42 + 0.3722, with a coefficient of determination (R2) of 71.48%). The regression analysis between cut weight and back fat thickness was Y = 0.322 + 0.04044, with a coefficient of determination (R2) of 39.87%, which means that cutting weight has a very significant effect (P <0.01) on the thickness of back fat, while the regression analysis of the relationship between cut weight and pH Local pork is Y = 6.357 - 0.00362, with a coefficient of determination (R2) of 5.54% that the slaughter weight has no significant effect (P> 0.05) on meat pH. Cut weight has no significant effect (P> 0.05) on cooking loss based on regression analysis is Y = 30.12 - 0.1106 with a coefficient of determination (R2) 9.63%. The results showed that cut weight has a close relationship with carcass weight, carcass length, and fat thickness but not to carcass percentage, meat pH and cooking loss.